2021
DOI: 10.24908/pceea.vi0.14827
|View full text |Cite
|
Sign up to set email alerts
|

Use of Electrodermal Wristbands to Measure Students' Cognitive Engagement in the Classroom

Abstract: A pilot project was conducted to study the feasibility of using electrodermal activity sensors embedded in a watch-like device to measure skin conductivity in real time. In the field of education, it may be interesting to use this technology to assess the students' cognitive engagement in the classroom. A few volunteer students as well as the professor were wearing an Empatica E4 wristband during some class periods where different activities were organized such as lectures, workshops and exams. Monitoring seve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Wearables such as the Empatica E4 have been used to measure electrodermal activity, skin temperature, and heart rate [11]. Some have linked wearable data to engagement [17][18][19], while others have used the data as indexes or measures of mental effort, mental workload, or cognitive load (for the purposes of this paper, we use these terms synonymously, referring to the load placed on the working memory during a task). Based on existing research, we believe that mental effort or mental workload is an appropriate correlate [1] to physiological activity, because mental workload demands can cause an unconscious, automatic response by the autonomic nervous system [20].…”
Section: Review Of Literature 21 the Use Of Wearables In Educationmentioning
confidence: 99%
See 2 more Smart Citations
“…Wearables such as the Empatica E4 have been used to measure electrodermal activity, skin temperature, and heart rate [11]. Some have linked wearable data to engagement [17][18][19], while others have used the data as indexes or measures of mental effort, mental workload, or cognitive load (for the purposes of this paper, we use these terms synonymously, referring to the load placed on the working memory during a task). Based on existing research, we believe that mental effort or mental workload is an appropriate correlate [1] to physiological activity, because mental workload demands can cause an unconscious, automatic response by the autonomic nervous system [20].…”
Section: Review Of Literature 21 the Use Of Wearables In Educationmentioning
confidence: 99%
“…The second prominent challenge researchers face is how to best analyze the data from wearables in educational contexts. Some researchers have analyzed physiological variables individually, such as heart rate, electrodermal activity, or skin temperature [18,24,25]. However, a recent systematic review revealed that there was no single physiological measure that captured all aspects of mental workload measurement [21].…”
Section: Review Of Literature 21 the Use Of Wearables In Educationmentioning
confidence: 99%
See 1 more Smart Citation